Evaluation of Natural Spring Freeze Tolerance of Five Pecan Scion–Rootstock Combinations - Amandeep Kaur; Lu Zhang; Ming Yang; Niels Maness; Charles J. Graham; Rashmi Kumari; Yanwei Sun; Srijana Panta; Louise Ferguson (HortScience, 2023)
Pecan [Carya illinoinensis (Wangenh.) K. Koch] is a member of the Juglandaceae family. During spring, pecan trees break their bud dormancy and produce new leaves and flowers. Carbohydrates stored in roots and shoots are thought to support the bloom and early vegetative growth during this time until new leaves start the full photosynthetic activity. Spring freeze is known for its damaging effects on pecan bud and flower growth and development. Pecan shoots with leaves and flowers from five scion–rootstock combinations were collected hours before and after a recent spring freeze (below 0 °C for 6 hours, 21 Apr 2021, Perkins, OK, USA). Morphologies of the leaf, bud, and catkin were visually observed, and the morphologies of the anther and pollen in paraffin sections were investigated by light microscopy. Soluble sugar and starch from bark and wood were analyzed using the anthrone reagent method. The Kanza–Mount showed the maximum damage to terminal leaves, buds, and catkins, whereas Maramec–Colby had the minimum damage only to leaves. Pollen grains were shrunk and reduced in number in the anthers in the protandrous Pawnee scions, whereas no pollen damage was observed in the protogynous Kanza scion. Furthermore, bark soluble sugar levels increased in all the scion–rootstock combinations after the freeze, which may indicate a physiological response to the cold stress. Overall, the extent of spring freeze damage of pecans is affected by the growth stage, types of scion and rootstock, and the scion–rootstock interactions. Furthermore, in addition to low temperature, scion–rootstock interactions also affected the starch and soluble sugar contents in wood and bark tissues.